Creating good habits: making reflection the norm. (2nd June 2019) - Power, Alison; Roberts, Alice
Abstract : The Nursing and Midwifery Council (NMC) states that midwives should reflect on their practice in order to highlight areas where changes might lead to improvements in future. The NMC Code also states that midwives must be aware of, and mitigate as far as possible, any potential harm associated with practice. The importance of reflection cannot be underestimated in relation to providing high quality, safe and effective care in line with the standards expected by the NMC, employers and service users. A previous article in this series discussed an innovative e-module supporting student midwives' employability, social awareness and preparedness for professional practice on qualification. This article will review the e-module through a different lens: that of the student. Alice will share her experiences from the student's perspective of how she feels engagement with this module will impact on her employment opportunities and future practice.